2001
DOI: 10.1590/s0004-282x2001000400012
|View full text |Cite
|
Sign up to set email alerts
|

Bloqueio anestésico do nervo occipital maior na profilaxia da migrânea

Abstract: RESUMO -Na fisiopatologia da enxaqueca muitas estruturas estão envolvidas, sendo que o nervo trigêmeo pode ser considerado a estrutura principal. Com o objetivo de determinar a influência do nervo occipital maior (NOM) sobre o comportamento da enxaqueca, estudamos 37 pacientes que apresentavam crises de enxaqueca. Utilizando-se de um estudo duplo cego cruzado os pacientes foram submetidos a infiltração do NOM com bupivacaína 0,5% (BP) e soro fisiológicos 0,9% (S.), os efeitos clínicos após os bloqueios anestés… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Traditionally, the treatment of migraine through GON blocks has relied on observational studies (33)(34)(35)(36)(37) as controlled clinical trials have been scarce. In 2001, Piovesan et al carried out the first double-blind clinical trial against placebo for GON block as a preventive treatment in migraine (26). A sample of 37 patients with EM and low or moderate monthly frequency of attacks (mean 3.6 days per month, range 1-8) underwent a sham procedure and GON block in a cross-over design, with a 30-day interval between interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, the treatment of migraine through GON blocks has relied on observational studies (33)(34)(35)(36)(37) as controlled clinical trials have been scarce. In 2001, Piovesan et al carried out the first double-blind clinical trial against placebo for GON block as a preventive treatment in migraine (26). A sample of 37 patients with EM and low or moderate monthly frequency of attacks (mean 3.6 days per month, range 1-8) underwent a sham procedure and GON block in a cross-over design, with a 30-day interval between interventions.…”
Section: Discussionmentioning
confidence: 99%
“…GON blocks with local anaesthetics and/or corticosteroids have been employed for decades in the acute and prophylactic treatment of migraine and other headache disorders (24,25). However, only three randomised, placebo-controlled trials examining the effect of GON blocks in patients with migraine have been published (26)(27)(28); these trials had contradictory conclusions and only one of them was focused on CM.…”
Section: Introductionmentioning
confidence: 99%
“…No statistically significant difference was found in the duration or number of episodes (16). Blockade of GON with lidocaine was reported to stop migraine attacks in 88% of a patient group (22).…”
Section: Discussionmentioning
confidence: 77%
“…Although these agents are thought to have similar effects, the different local anesthetics used make comparison between studies difficult. After bupivacaine (15,16), lidocaine is the second most commonly used drug for migraine (12)(13)(14)4,5); some studies used a combination of these two drugs (4). Ashkenazi et al found no difference in the outcome of greater occipital nerve blockade for headache with lidocaine and bupivacaine alone or with the same agents with the addition of a steroid drug.…”
Section: Discussionmentioning
confidence: 99%
“…Revista Multidisciplinar do Nordeste Mineiro, v.2 2021/02 ISSN 2178-6925 A fisiopatologia da migânea ainda não é totalmente esclarecida, porém acredita-se que ela inicia-se com um estimulo nervoso, externo ou interno, que levaria a uma chamada depressão cortical alastrante (DA), geralmente com foco inicial no lobo occipital e que se propagaria para o restante do córtex sem seguir preferencialmente os trajetos dos nervos, essa depressão é causada por uma hipoperfusão devido à vasoconstrição arteriolar, e explicaria os fenômenos da aura enxaquecos (VINCENT, 1998). Além disso, acredita-se que a aura é seguida por hiperemia e essa alterações não parecem se correlacionar com a fase da dor de cabeça (PAHIM; MENEZES; LIMA, 2006;PIOVESAN et al, 2001;GOLDMAN;AUSIELLO, 2005;PIOVESAN et al, 2000).…”
Section: )unclassified